Identifying and treating postanesthesia emergencies. Issue 6 (30th November 2015) - Strauss, Penelope Z.; Lewis, Matthew M.
Abstract : Postanesthesia care unit (PACU) nurses encounter many emergencies. Three of the most critical events that PACU nurses face requiring emergency intervention are: residual neuromuscular blockade, acute postoperative hypertension and acute hypotension.